Pengaruh Flash Sale, FOMO dan Digital Financial Literacy Terhadap Impulsive Buying - Sari, Fitri Raisya; Sanistasya, Poppy Alvianolita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The rapid growth of e-commerce and social media integration has significantly transformed consumer purchasing behavior, especially among digital-native generations. Generation Z, known for their strong online presence and responsiveness to trends, is particularly vulnerable to impulsive buying triggered by online marketing strategies. This study aims to examine the influence of flash sales, Fear of Missing Out (FOMO), and digital financial literacy on impulsive buying behavior among Generation Z users of TikTok Shop X Tokopedia in Samarinda, Indonesia. The research involved 106 respondents selected through purposive sampling. Data were collected using structured questionnaires and analyzed through multiple linear regression using SPSS software. The results show that FOMO has a significant and positive effect on impulsive buying, whereas flash sales and digital financial literacy do not have significant individual effects. However, when combined, all three variables significantly influence impulsive buying, accounting for 42.2% of the behavior variance. These findings highlight the psychological and emotional factors—particularly FOMO—as more dominant drivers than promotional or financial literacy factors. The study suggests that understanding these behavioral dynamics is essential for businesses targeting young online consumers, while also underscoring the need for improved digital financial awareness among youth.